THE ISSUES OF PROVIDING MEDICAL SERVICES TO THE POPULATION IN THE VILLAGES OF ANDIZHAN REGION - Abdurakhmon Abdumuminovich Abdukhalimov (EPRA International Journal of Research and Development (IJRD), 2022)
The article covers the issues of providing medical services to the population in the villages of Andizhan region, protecting the health of the population, and providing them with quick and high-quality medical care. Also, the work carried out by doctors and nurses was studied, and the activity of outpatient clinics was analyzed.